Proses Kreatif Penciptaan bawor - Budi Hartono (Ars: Jurnal Seni Rupa dan Desain, 2011)
Bawor Character Creation Process. The classical shadow play with leather puppets that has been acknowledged as a cultural heritage coming from Indonesia is potential to compete in global level. Bawor, one of the punakawan characters in Banyumasan leather puppet show, has a similar physical appearance with Semar who adopted him as a son. Bawor’s character is considered to be identical with the character of Banyumas people, for example they are believed to be honest. The works of art that have been inspired by Bawor show some form transformations. The form is changed to get funny impression. However, there are still certain messages to be delivered by means of those funny forms. Although there are many possible interpretation, but visually those figures still can be identified as the fat Bawor. So far, craft is regarded as identical with ornament. These Bawors that were depicted without ornamentwere an adjustment to the visual art development nowadays.Keywords: Bawor, craft, ornament